Intravenous immunoglobulins control scleromyxoedema. Issue 1 (1st January 2002) - Righi, A; Schiavon, F; Jablonska, S; Doria, A; Blasczyk, M; Rondinone, R; Todesco, S; Cerinic, M Matucci
Abstract : Background: Scleromyxoedema is a variant of papular mucinosis affecting the skin and internal organs. The different therapeutic approaches proposed for scleromyxoedema are still unsatisfactory. Intravenous immunoglobulin (IVIg) has been successfully employed in the treatment of connective tissue diseases and vasculitides. Patients: The successful treatment of three cases of scleromyxoedema with IVIg is reported here. Conclusions: The relatively low risk of the drug and the high effectiveness seen in three patients suggest that IVIg is a new treatment potentially useful in scleromyxoedema.